Evolución de los Cuerpos Académicos en la Universidad de Guanajuato - Catalina Martínez, Patricia; Rico Venegas, Rosa María; Preciado Tarabay, Salma Evelia (Acta Universitaria, 2006)
The members of the Academic Community have slowly placed themselves in the local and national scene. They work towards a universal educational goal. This requires the renewal of systems and strategies to create knowledge adaptable to the dynamic changes of a globalized world. The quality of higher education depends on many factors, one of the most important, is the professor; as such, the Academic Community takes seriously the professor’s tenure track as well as the overall education. This education implies a deep conceptual understanding of taught academic disciplines, this ideally is demonstrated by the completion of a PhD degree. This is why the University of Guanajuato has placed emphasis on the conformation of Academic Communities. Furthermore, permanent support to the faculty is offered to study graduate degrees with the idea of creating and applying new knowledge and offering them the installations that wil allow them to fulfill their academic functions. The perseverance of the work of the Academic Communities has contributed to their consolidaton in such a way that in 2002 there were only five Academic Communities and now a day there are 14.
Keywords: Array; Array; Array